2015
DOI: 10.1159/000368418
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences of ≥pT1 Bladder Cancer Survival in Austria: A Descriptive, Long-Term, Nation-Wide Analysis Based on 27,773 Patients

Abstract: Introduction: In recent days, the relationship between gender, tumour stage and survival of bladder cancer has attracted interest. Materials and Methods: The Austrian cancer registry was linked to the national death statistics. All patients with urothelial cancer of the urinary bladder with stages pT1, pT2, pT3 and pT4 diagnosed between 1983 until 2012 were followed for up to 15 years. Overall and cancer-specific mortality were estimated by cumulative incidence. Results: A total of 27,773 patients were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Furthermore, many series are hampered by the limited sample size due to the low incidence of UTUC; however, the two largest, population-based studies in this respect support this gender-specific stage shift in UTUC. Our group has recently reported a similar phenomenon by analysing 27,733 patients with bladder cancer in Austria [15]. It has been postulated that a gender-specific referral pattern might be a major factor for the stage shift in women with bladder cancer [16] and one can speculate that the same also applies for UTUC.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, many series are hampered by the limited sample size due to the low incidence of UTUC; however, the two largest, population-based studies in this respect support this gender-specific stage shift in UTUC. Our group has recently reported a similar phenomenon by analysing 27,733 patients with bladder cancer in Austria [15]. It has been postulated that a gender-specific referral pattern might be a major factor for the stage shift in women with bladder cancer [16] and one can speculate that the same also applies for UTUC.…”
Section: Discussionsupporting
confidence: 57%
“…We have adjusted the effect of age in a descriptive and a statistical-inferential way. The statistical analyses, however, were hampered by the relatively low number of events particularly per stage group, when comparing the results, e. g. to a similar analysis of our group of bladder cancer patients using a 10-fold larger data base [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Another survey of over 20,000 patients from the Netherlands Cancer registry reported a higher rate of advanced tumour stages in women [5]. In a nationwide Austrian study on bladder cancer, Waldhoer et al [13] have demonstrated that the men-to-female ratio declined constantly from 3: 1 for pT1 tumours to 1.9: 1 in those with pT4 tumours. It remains controversial whether women have a worse prognosis when treated, for example, by RC if the stage-shift at diagnosis is taken into account [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Most large studies refute this, however, with evidence that women not only present with more advanced tumors than their male counterparts [8,21,22,23,24,25,26], but are also more likely to have nodal involvement at diagnosis [8,23,27]. …”
Section: Does the Stage Of Cancer Differ At Diagnosis?mentioning
confidence: 99%